Fork me on GitHub
Math for the people, by the people.

User login

How does Cauchy's inequality work?

Primary tabs

How does Cauchy's inequality work?

cauchy's inequality is supposed to be:

(xy^3+yz^3+zx^3)(z+x+y) *is greater than or equal to* xyz(y+z+x)^2.

i don't get what it's supposed to be used for, and how it works. it just confuses me. please help!!!

thanks!!!


Hi, it is the squared special instance n=3, x,y,z>=0,

(x1,x2,x3)=(sqrt(xy^3),sqrt(yz^3),sqrt(zx^3)),
(y1,y2,y3)=(sqrt( z ),sqrt( x ),sqrt( y )),

x*y =(sqrt(xyz)y,sqrt(xyz)z,sqrt(xyz)x),
x.y = sqrt(xyz)(y + z + x).

Given x=0, z=1, the inequality reads

y(1+y)>=0 and fails for 0>y>-1, so nonnegativity is necessary.

Greetings,
Andy.

(x+y+z)\neq 0 it is innecesary and (x+y+z)=0 is trivial.

Subscribe to Comments for "How does Cauchy's inequality work?"